(Dicyclopentadiene) platinum(II) dichloride: An efficient catalyst for the hydrosilylation reaction between alkenes and triethoxysilane. Issue 16 (19th April 2017) - Wu, Huarui; Zheng, Chaoyue; Chen, Naiwu; Zhu, Jie; Gao, Deqing
Graphical abstract: (Dicyclopentadiene) platinum(II) dichloride [Cp2 PtCl2 ] was found to be an efficient catalyst for the hydrosilylation reaction between alkenes and triethoxysilane. Highlights: Efficient hydrosilylation catalyst between alkenes and triethoxysilane. High performance of the hydrosilylation of triethoxysilane in terms of yield and selectivity. Developing the hydrosilylation of the protected diamino chelating alkene. Abstract: (Dicyclopentadiene) platinum(II) dichloride was found to be an efficient hydrosilylation catalyst (homogeneous) upon a wide variety of functionalized alkenes and alkenes terminated with chemical moieties (diphenyl amino-, N -carbazol- and N -isoindoline-1, 3-dione-). It is noteworthy that the hydrosilylation of aminated alkenes with triethoxysilane exhibited the yield of over 70% and the selectivity (γ-isomer/β-isomer) of more than 3/1. Due to steric hindrance lowering Markovnikov probability, the alkenes with big terminal moieties (diphenyl amino-, N -carbazol- and N -isoindoline-1, 3-dione-) presented the high ratio of anti-Markovnikov isomers. The strategy of the hydrosilylation of the protected diamino chelating alkene was developed.